The psychological effects of social distancing caused by the new Coronavirus in university students (Research, Society and Development, 2021)
Social distancing measures implemented to curb the spread of the new coronavirus can have a disastrous result and trigger negative psychological effects. College students seem to be particularly impacted by the restrictions arising from COVID-19. In this scenario, the aim of this study was to analyze the psychological effects of social distancing resulting from COVID-19 in undergraduate students. This is a narrative review of the literature, carried out from the search for scientific articles in the PubMed, Scielo and Science Direct databases, published in the period 2020 and 2021, using the descriptors "Coronavirus", "Covid-19", “Social Isolation”, “Mental Health” and “Students”. The results suggest that university students already have a tendency to develop psychiatric disorders and that the outbreak of COVID-19 further accentuated mental suffering in this population, indicating that the social distance resulting from the current pandemic can have a strong influence on psychological health and that women and younger people are at increased risk for developing disorders. However, it is not possible to conclude that, by itself, social distancing is capable of inducing psychological distress, denoting the need for further studies that consider this aspect.